Digitalisasi Literasi Sekolah: Dampak Implementasi QR Code E-Book terhadap Minat Baca Siswa SMA - Ayu Dewanti; Slamat Baniruddin; Rifa Azmi Fadhillah; Muhammad Aldi; Januar Abdilah Santoso; Yeni Rahmawati; Chienda Alfino Rinaldy (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The goal of this community service program (PkM) at SMA Negeri 11 Samarinda is to increase students' enthusiasm for reading by providing them with e-books that are based on QR codes. Students' lack of enthusiasm for reading and resources for reading led to the program's inception. E-books with QR codes embedded were presented as a workable approach to digital literacy that caters to the needs of students who were born into the digital age. Several steps were involved in the process, such as determining requirements, creating an e-book, creating QR codes, installing them at key school locations, and finally, monitoring and evaluating the results. Observations and questionnaires were given to 200 students as part of the assessment. Students' interest in and ability to access literature were both enhanced by the usage of QR Codes, according to the findings. In a survey, 82% of people said QR Codes were simple to use, and 85% said they were more motivated to read after using them. In terms of reading frequency, 76% of students saw an improvement, and 72% said they could understand what they read better.With an overall mean score of 4.35 (categorized as excellent), the digital literacy program proved to be effective and positively received. Overall, the implementation of QR Code–based e-books successfully strengthened digital literacy practices and created a more engaging, flexible, and sustainable reading experience, offering a model for digital literacy initiatives in other schools.